PENGARUH LEVERAGE, UKURAN PERUSAHAAN, USIA DEWAN KOMISARIS DAN USIA DEWAN DIREKSI TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN YANG TERDAFTAR DALAM DAFTAR EFEK SYARIAH PERIODE 2019-2021: PENGARUH LEVERAGE, UKURAN PERUSAHAAN, USIA DEWAN KOMISARIS DAN USIA DEWAN DIREKSI TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING DENGAN PERTUMBUHAN LABA SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN YANG TERDAFTAR DALAM DAFTAR EFEK SYARIAH PERIODE 2 - Komariah, Rizka (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2022)
This study aims to investigate the impact of leverage, company size, age of the board of commissioners, and size of the board of directors on Islamic Social Reporting (ISR) disclosure. The study also considers profit growth as a moderating variable. The research focuses on companies listed on the Sharia Securities List from 2019 to 2021. A total of 537 research data points were collected over a 3-year period using purposive sampling techniques to select 179 companies from a population of 246 companies. The study employed the Random Effects Model approach for panel data regression to test hypotheses and the Moderated Regression Analysis (MRA) model to examine the moderating variable. The Eviews program version 10 was used for data analysis. The results indicate that leverage has a negative effect on ISR disclosure, while company size does not significantly affect ISR disclosure. The age of the board of commissioners has a negative impact on ISR disclosure, whereas the size of the board of directors positively influences ISR disclosure. The relationship between leverage and ISR disclosure is strengthened by profit growth moderation. However, profit growth does not moderate the effect of company size or the age of the board of commissioners on ISR disclosure. The moderation effect of profit growth is also absent in the relationship between the age of the board of directors and ISR disclosure.